Pengaruh Influencer Marketing dan Live Shopping Pada Tiktokshop Terhadap Keputusan Pembelian Produk â€œEat Sambelâ€ - Susilo, Kristianto (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the influence of influencer marketing and TikTok Shop on increasing sales of "Eat Sambel" products. Influencer marketing has become a popular marketing strategy in the digital industry, with the increasing use of social media as a promotional tool. TikTok Shop, as a commerce feature of the TikTok platform, has also become a fast-growing trend of selling products directly to users. The research method used in this study is distributing questionnaires to consumers who have been involved in purchasing the "Eat Sambel" product. The collected data was analyzed using regression analysis to test the influence of the independent variables, namely influencer marketing and use of TikTok Shop, on the dependent variable, namely increasing product sales.